PPARγ agonists delay age‐associated metabolic disease and extend longevity. Issue 11 (21st November 2020) - Xu, Lingyan; Ma, Xinran; Verma, Narendra; Perie, Luce; Pendse, Jay; Shamloo, Sama; Marie Josephson, Anne; Wang, Dongmei; Qiu, Jin; Guo, Mingwei; Ping, Xiaodan; Allen, Michele; et al.
Abstract: Aging leads to a number of disorders caused by cellular senescence, tissue damage, and organ dysfunction. It has been reported that anti‐inflammatory and insulin‐sensitizing compounds delay, or reverse, the aging process and prevent metabolic disorders, neurodegenerative disease, and muscle atrophy, improving healthspan and extending lifespan. Here we investigated the effects of PPARγ agonists in preventing aging and increasing longevity, given their known properties in lowering inflammation and decreasing glycemia. Our molecular and physiological studies show that long‐term treatment of mice at 14 months of age with low doses of the PPARγ ligand rosiglitazone (Rosi) improved glucose metabolism and mitochondrial functionality. These effects were associated with decreased inflammation and reduced tissue atrophy, improved cognitive function, and diminished anxiety‐ and depression‐like conditions, without any adverse effects on cardiac and skeletal functionality. Furthermore, Rosi treatment of mice started when they were 14 months old was associated with lifespan extension. A retrospective analysis of the effects of the PPARγ agonist pioglitazone (Pio) on longevity showed decreased mortality in patients receiving Pio compared to those receiving a PPARγ‐independent insulin secretagogue glimepiride. Taken together, these data suggest the possibility of using PPARγ agonists to promote healthy aging and extend lifespan. Abstract : In this manuscript, we show that chronic use of low doses of antidiabetic drugs that target the nuclear receptor PPARgamma preserves metabolic organ function and cognitive abilities and decreases depression‐ and anxiety‐like symptoms. Through functional, histological, and molecular analyses, we demonstrated that treated mice have improved adipose tissue homeostasis, reduced sarcopenia, decreased inflammation, and improved mitochondrial functionality. In addition, our longevity studies demonstrated lifespan extension in mice and increased survival in humans in response to TZD. These data support the possible long‐term use of low doses PPARgamma ligands to counteract aging.